2021
DOI: 10.1021/acs.jpcc.0c10882
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and Spectroscopic Analyses of Zirconium Phosphate-Absorbed Ammonia

Abstract: Zirconium phosphate is insoluble in water and has a large ammonia storage capacity with a low ammonia plateau concentration in water. In this study, the thermodynamics of ammonia on zirconium phosphate (ZrP) and the local structure such as the interaction between ammonia and ZrP have been investigated using the temperature dependence of ammonia concentration composition isotherm (CCI) measurements, 31 P magic angle spinning nuclear magnetic resonance ( 31 P MAS NMR), and Fourier transform infrared (FT-IR) spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Variations in 31 P chemical shift for the hydrated and anhydrous zirconium phosphate intercalates have been interpreted earlier in terms of hydrogen bonds, formed by the interlayer phosphate group, where a donor hydrogen bond leads to displacement Δδ (iso) of $ 3 ppm, while Δδ (iso) of approximately À2 ppm corresponds to an acceptor hydrogen bond. [16] Following this rule, the low-field resonance of HPO 4 groups at δ of À21.4 ppm could be attributed to hydrogen bond P OH˙˙˙OD 2 [11] (Figure 1). Upon formation of such a bond, rates of rotations around the P O axis in the structurally different HPO 4 groups of compound 1-D 2 O, which cause phosphorus NMR relaxation by the dipolar proton-phosphorus mechanism, [17] will have to differ.…”
Section: Resultsmentioning
confidence: 82%
“…Variations in 31 P chemical shift for the hydrated and anhydrous zirconium phosphate intercalates have been interpreted earlier in terms of hydrogen bonds, formed by the interlayer phosphate group, where a donor hydrogen bond leads to displacement Δδ (iso) of $ 3 ppm, while Δδ (iso) of approximately À2 ppm corresponds to an acceptor hydrogen bond. [16] Following this rule, the low-field resonance of HPO 4 groups at δ of À21.4 ppm could be attributed to hydrogen bond P OH˙˙˙OD 2 [11] (Figure 1). Upon formation of such a bond, rates of rotations around the P O axis in the structurally different HPO 4 groups of compound 1-D 2 O, which cause phosphorus NMR relaxation by the dipolar proton-phosphorus mechanism, [17] will have to differ.…”
Section: Resultsmentioning
confidence: 82%
“…Then, zirconium phosphate with different ammonia absorption capacities was prepared by vacuum drying for at least half a day. At this time, it has been confirmed that the ammonia and crystalline water in the samples are hardly released, and the water on the surface of the samples is removed. , …”
Section: Methodsmentioning
confidence: 78%
“…Zr(HPO 4 ) 2 ·H 2 O showed the greatest amount of ammonia absorption among insoluble ammonia absorbing materials such as Prussian blue. 13 , 15 , 16 However, there is no research on recycling back to Zr(HPO 4 ) 2 ·H 2 O after regeneration of [Zr(NH 4 PO 4 ) 2 ·H 2 O].…”
Section: Introductionmentioning
confidence: 99%
“…Zr(HPO 4 ) 2 •H 2 O showed the greatest amount of ammonia absorption among insoluble ammonia absorbing materials such as Prussian blue. 13,15,16 However, there is no research on recycling back to Zr(HPO 4 ) In this report, we have studied a heat treatment method under an inert atmosphere to regenerate zirconium phosphate from ammonia-absorbed Zr(HPO 4 ) further purification. Various concentrations of ammonia water were prepared using 10 wt % ammonia water from KENEI Pharmaceutical Co., Ltd., diluting with ion exchange water.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation